An unusual depiction of Ba‘al Arwad and a hippocampus on coins of Arados during the Persian Period - Rowe, Martin (KOINON: The International Journal of Classical Numismatic Studies, 2019)
This essay documents three unusual tetrobols, minted during the Persian period of Arados. To the author’s knowledge, no prior studies have been conducted on these coins which were struck from a single die pair; for the duration of this essay they will be referred to as die pair 10.